2021
DOI: 10.1101/2021.06.11.21258575
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Support needs and barriers to accessing support: Baseline results of a mixed-methods national survey of people bereaved during the COVID-19 pandemic

Abstract: Background: The COVID-19 pandemic is a mass bereavement event which has profoundly disrupted grief experiences. Understanding support needs and access to support among people bereaved at this time is crucial to ensuring appropriate bereavement support infrastructure. Aim: To investigate grief experiences, support needs and use of formal and informal bereavement support among people bereaved during the pandemic. Design: Baseline results from a longitudinal survey. Support needs and experiences of accessing s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Participants were provided with a list of 17 informal, community, and formal supports adapted from previous research [ 1 , 13 ] and were asked to indicate those they had accessed following bereavement. Participants were then asked to select the support they perceived as most helpful.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were provided with a list of 17 informal, community, and formal supports adapted from previous research [ 1 , 13 ] and were asked to indicate those they had accessed following bereavement. Participants were then asked to select the support they perceived as most helpful.…”
Section: Methodsmentioning
confidence: 99%
“…This led to calls from grief researchers to prepare for a ‘silent epidemic of grief’[ 8 , 9 ]. Internationally several studies have found that pandemic-related challenges have impacted on the support needs of the bereaved and the support sources available [ 10 13 ]. The support needs of bereaved people in Australia during the pandemic have not been examined.…”
Section: Introductionmentioning
confidence: 99%